Phenoplastic Potentials of Cocoyam Species Exposed to Selected Environmental Stressors - Florence O. Ajah; Julian O. Osuji; Geoffrey O. Anoliefo (Progress in Chemical Science Research Vol. 8, 2023)
Investigation of the effects of two oilfield chemicals on the morphology of some cocoyam accessions was carried out. Accessions of Colocasia esculenta and Xanthosoma maffafa were exposed to graded concentrations of sodium thiosulphate and graphite powder. The following concentrations (5, 10, 20 and 400 mg/kg) of sodium thiosuphate and graphite powder respectively were applied to the accessions while unpolluted soil served as the control experiment. Observations revealed that the polluted accessions had increased plant heights and better yields than the control. Some X. maffafa accessions polluted with sodium thiosulphate produced malformed leaves. Cocoyam accessions generally demonstrated poor environmental bioindicator potentials hence, soil assessments and further studies on lands that would be used for cocoyam cultivation were advocated.